Managing Director's Statement to the Development Committee. (Policy Papers; Policy Paper ;, 2005)
Our meeting takes place at an important juncture in the international community's efforts towards achieving the Millennium Development Goals (MDGs). It is now five years since we took up this enormous challenge, and there is a sense of renewed urgency. The recent UN World Summit on Implementing the Millennium Declaration reaffirmed the commitments made in Monterrey, but stressed the need for more progress, particularly in Sub-Saharan Africa. In addition, at the African Union and G-8 Summits, African leaders and their counterparts in the G-8 committed themselves to intensify their efforts.